Research Trends in Talent Management and Career Development: Why is Promotion Important? (Bibliometric Analysis) - Putra Satriya Yudha; Rr. Sri Handari Wahyuningsih; Retno Widowati (Universitas Muhammadiyah Ponorogo, 2023)
This study looks for connections between global career development and trends in talent management research. Â In the context of TM, career development plays an important role. This is because individual careers have significant potential to serve organizational strategic goals. After all, investment in organizational career development is beneficial not only for individuals, but also for organizational performance. For this research, the author processes Scopus index journal data using VOSviewer. This study used VOSviewer to analyze the data and map the most general and well-liked focal topics. 192 research papers in RIS format were used in this study. The Scopus database shows a fluctuation in the amount of research done on talent management and career development over the last few years and a decline in that interest. Â The VOSviewer analysis map classifies the most prominent nodes so that the most significant influence is the